Five new species of the genus Noeetomima Enderlein (Diptera: Lauxaniidae) from China, with a key to world species - Li, Wenliang; Chen, Xulong; Yang, Ding (Zootaxa, 2020)
Five species of Noeetomima Enderlein, 1937 from Southwest China are described as new to science: Noeetomima hongshanensis sp. nov., N. lijiangensis sp. nov., N. liui sp. nov., N. trisurstyla sp. nov. and N. zhangae sp. nov.. A key to world species of the genus Noeetomima is presented. The specimens studied are deposited in the Entomological Museum of China Agricultural University, Beijing, China (CAUC).